Comparing nitrate leaching between contemporary and regenerative dairy pasture management : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science, Agricultural Science at Massey University, Manawatū, Palmerston North, New Zealand - Wittahachchi, Udara Dilhani (Massey University, 2025)
New Zealand’s dairy industry is crucial to the national economy, yet it faces significant environmental challenges, particularly nitrate (NO₃⁻) leaching from intensive pasture-based farming systems. The concentrated nitrogen (N) in urine patches left by grazing cows is the primary contributor to NO₃⁻ leaching in dairy pastures. While various mitigation strategies have been explored, many have come with limitations. Lower N input regenerative management has emerged as a potential approach to reduce NO₃⁻ leaching, particularly when combined with diverse pasture. More diverse pasture swards that include deeper-rooted species and herbs already known to reduce leaching have the potential to mitigate NO₃⁻ -N loss from NZ dairy systems. The measurement of NO₃⁻ leaching in free-draining soils is challenging due to the lack of methods that can accurately collect drainage at a scale representing the variability in a pasture paddock. Therefore, the objectives of this research were to 1) assess the effectiveness of trench lysimeters to measure drainage and NO₃⁻ leaching in a free-draining Manawatū sandy loam soil, 2) compare NO₃⁻ concentrations measured using trench lysimeters with a suction cup array, and 3) evaluate and compare NO₃⁻ leaching under three pasture management systems: standard pasture with contemporary management (Std-Con), diverse pasture with regenerative management (Div-Reg), and diverse pasture with contemporary management (Div-Con). The research was conducted over a period of two years (2023 and 2024) at Dairy One farm at Massey University near Palmerston North, utilising 12 trench lysimeters and 90 suction cups on three different pasture treatments, namely Std-Con, Div-Reg and Div-Con. Contemporary management follows DairyNZ best practices with lower post-grazing residuals and uses mineral/synthetic fertilisers and chemical sprays as needed. Regenerative management involves longer grazing intervals, higher post-grazing residuals, and reduced use of mineral/synthetic fertilisers and chemical sprays. The four trench lysimeters per treatment reliably measured drainage depths with generally low standard errors across different drainage events, indicating their reliability for measuring drainage in free-draining soils. Compared to trench lysimeters, suction cups were less effective, recording significantly lower NO₃⁻-N concentrations with higher variability. In cases where suction cup NO₃⁻ -N concentrations were high; this was likely due to individual urine patches resulting in large variability between replicates. In both years, the Div-Con treatment had the highest NO₃⁻- N load, followed by Std-Con and Div-Reg; however, unusually elevated NO₃⁻-N concentrations in two lysimeters associated with the Div-Con treatment were responsible for this effect. Therefore, further investigation is required to verify the results from this treatment. In 2023, NO₃⁻ N loads were 3 and 14 kg N/ha for Div-Reg and Std-Con, respectively. In 2024, the values increased to 5 and 24 kg N/ha. Both methods indicated a declining trend in NO₃⁻-N concentrations across all treatments as the drainage season progressed. Compared to the Std-Con treatment, the Div-Reg treatment consistently measured only 21.4% and 20.8% of NO₃⁻-N leaching in 2023 and 2024, respectively, but further monitoring is needed to address the challenges identified in this study and to more thoroughly assess differences between treatments.
Keywords: 300202 Agricultural land management; 300404 Crop and pasture biochemistry and physiology